Viability of a nutrition programme in Guyana. - CHELLARAJ, G. (1993)
Develops a proposal to study the impact of the Economic Recovery Programme on the health and nutritional status of the population in Guyana, and its impact on productivity and economic growth. Discusses food subsidy programmes in other developing countries.